PEMIKIRAN RANGGAWARSITA SEBAGAI BAHAN AJAR PENDIDIKAN KARAKTER - - Purwadi (Fakultas Bahasa Seni dan Budaya, 2015)
Ranggawarsita is the great writer, who created much literature. He become pujangga by Kraton Surakarta in Sunan Paku Buwana IX goverment era. The Javanese people believe that Ranggawarsita has skill to read future signal. This is called Ramalan Ranggawarsita that wrotten in Serat Kalatidha. That book is often read to see social situation. As palace writer, Ranggawarsita is so make Serat Pustaka Raja that fill history of Java. there are say about mithology, spirituality, morality adn society. Serat Wirid Hidayat Jati written by Ranggawarsita aim to gibe description about harmonity between moslem doctrin and Javanese culture that can used to teach character education.Keywords: Ranggawarsita, liteture, character education